THU0154 PERCEPTIONS ABOUT INTERVENTIONS TO ENHANCE INFLUENZA VACCINE UPTAKE DIFFER BETWEEN VACCINATED AND UNVACCINATED RA/JIA PATIENTS. (2nd June 2020) - Valerio, V.; Bazan, M.; Wang, M.; Mazer, B.; Hazel, E. M.; Pineau, C.; Bernatsky, S.; Colmegna, I.
Abstract : Background: To optimize the control of vaccine preventable diseases, high immunization coverage rates must be achieved. Influenza vaccination rates among patients with rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) are suboptimal. Understanding patient preferences for interventions that may increase vaccine uptake is the first step to inform the development of specific strategies to enhance vaccine coverage in RA/JIA. Objectives: To compare the perceptions of vaccinated and unvaccinated RA/JIA patients on a multi-modal intervention to enhance seasonal influenza vaccine coverage. Methods: During the 2018-2019 influenza season, a multi-modal intervention was implemented at a large Canadian academic center. This consisted of (i) a letter sent from the Division of Rheumatology to patients addressing common misconceptions about flu vaccines and encouraging patients to plan for immunization; (ii) a nurse providing inactivated influenza vaccine at the rheumatology clinics for the first 7 weeks after the vaccine was released, and (iii) clinics posters specifically designed for rheumatic patients and rheumatologists to prompt a discussion on influenza prevention. Patients that were vaccinated on site completed a survey evaluating the relevance of the individual components of the intervention. After the intervention, during a scheduled rheumatology visit, RA/JIA patients were asked to complete a similar survey. We compared the responses from RA/JIA patients that were vaccinated at our institution, to those of patients that reported not having received the influenza vaccine in 2018-2019. Results: During the intervention, 116 immunized RA/JIA patients completed the first survey. Forty RA/JIA patients not vaccinated during the 2018-2019 season completed the post-intervention survey. Both vaccinated and unvaccinated groups were mostly female (74.1% versus 87.2%), but vaccinated patients were older (50.8±19.4 versus: 40.5±14.9; 95% CI 3.7%, 17%), and had shorter disease duration (10.1±9.3 versus 15.0±9.8; 95% CI -8.9%, -1.1%) than those not vaccinated. Unvaccinated patients were less likely than vaccinated patients to approve of the clinic's provision of influenza vaccine (98.2% versus 75%; 95% CI 12.8%, 43.5%). When asked about elements of the intervention, unvaccinated patients were less likely than vaccinated patients to consider posters (65.2% versus 38.9%; 95% CI 7.9%, 42.9%), letters (69.4% versus 35.3%; 95% CI 16.2%, 51.2%), or phone calls (58.0% versus 41.7%; 95% CI 2.1%, 33.5%) as good reminders. Conclusion: Unvaccinated RA/JIA patients' opinions about interventions to increase vaccine uptake differ from vaccinated patients. Alternative, novel strategies to target vaccine hesitant RA/JIA patients are needed to optimize vaccine coverage. Disclosure of Interests: None declared